EMPOWERING 21ST CENTURY SKILL IN DISTANCE LEARNING THROUGH ELECTROLYTE SOLUTION ASSIGNMENTS AT SMAN 2 CIKAMPEK - Abdul Rosid (Universitas Negeri Surabaya, 2022)
The research aims to capture the ability and measure the collaboration index of students in conducting and presenting experimental results, involving 252 respondents using the case study method. The aspect of showing the ability to work effectively, being able to appreciate team differences has an index of 81.41% with a VERY STRONG interpretation,